Fractional modeling of temperature dynamics of a building with singular kernels - Acay, Bahar; İnç, Mustafa (Pergamon-Elsevier Science Ltd, 2021)
In the current study, the temperature dynamics of a building are proposed by means of some non-local singular fractional-order operators. In order to examine this model which has a crucial place in daily life, we utilize the Laplace transform. Accordingly, new analytical solutions including one, two, or three parameters are displayed to better control the non-renewable resources. One of the most remarkable features making the aforementioned model important is that it has different non-integer parameters a,., and., which enable us to approach maximum energy efficiency for buildings. Moreover, simulation analysis is carried out to observe the mobility of the solution curve in line with our objective. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Fractional derivatives; Energy-saving; Heating and cooling; Fractional modeling; Real-world problems